Volunteerism, compassion and religiosity as drivers of donations practices - Abreu, M. E.; Laureano, R. M. S.; Vinhas da Silva, R.; Dionísio, J. (International Journal of Non-profit and Voluntary Sector Marketing, 2015)
The topic of donations is one of high relevance and has been widely covered in contemporary marketing literature. It is a topic of interest to both theoreticians and practitioners alike, particularly due to its implicit links to fundraising activities and research. The reality of what makes an individual donor ultimately part with his money and give it away to a nonprofit organization is a hot contemporary topic. This study looks into the role of religiosity as a predictor of donations practices. Also volunteerism and compassion, two acts of pro-social behaviour are analysed as predictors of donations practices. Using data collected from a survey of 612 charity donors in Portugal, the results show unequivocally that religiosity does influence donations practices, and so being a predictor of donations practices. Moreover, pro-social behaviour is a predictor of donations practices when in the case of volunteerism, but not in the form of compassion. The findings are particularly useful for nonprofit organizations that want to attract and retain individual charitable donors and may also help to increase donation regularity, to obtain higher amounts, and donations both to religious and to secular organizations. Finally, it can be stated that the understanding of religiosity sheds light on knowledge about donations practices, and that this study also makes an important contribution to academia, as it is the first study conducted in Portugal that assesses the drivers of donations practices.